Dynamique et structure de la flore de la Savane Protégée des Feux dans la Réserve Scientifique de Lamto (Centre de la Côte d’Ivoire) - Gnahoré Eric; Missa Koffi; Koné Moussa; Gueulou Nina; Bakayoko Adama (European Scientific Journal, ESJ, 2018)
This work that is one of the first of its kind in Unburned Savannah in Lamto, center of Ivory Coast, intends to characterize the vegetation in terms of dynamic evolution and plant structure, 53 years after its protection from fires. Surfaces plot, linear surveys and itinerant methods were used to collect floristic data. The diversity and the wealth of flora, as well as the structure of the different types of vegetation has been analyzed. 176 plant species belonged to genera 143 kinds and 49 families were indentified. The most important families are the Leguminosae (14.77 %), Rubiaceae (13.63 %) and Apocynaceae (10.79 %). About 15.37 % (27 species) of this flora represents the particular statute species. Among the inventoried species, 11 are exploitable species or exploited as timber of which ten are forest species. Due to richnes of its flore and flora dynamic, the Unburned Savannah must be protected. Based on an ascending hierarchical classification performed by using 11 linear surveys, this study has demonstrated the existence of a floristic variability to three groups.